L'Art d'Aimer. (Sète : Nouvelle Vague - Chez le concierge, 1995)
Lin, Hila Lulu ; François, Pierre ; Guilleminot, Marie-Ange ; Lévêque, Claude ; Marsden, Stephen ; Bail, Jean-Pierre Le ; Magnin, André ; Okamo, Chieko ; Tsubaki Noboru ; Zush ; Pinaud, Pascal ; Talon-Giordano, Georgette ; Perramant, Bruno ; Renard, Joël ; Minako, Nishiyama ; Ming, Yan Pei ; Othoniel, Jean-Michel ; Mréjen, Valérie ; Hubaut, Joel ; Koo Jeong-a ; Jallais, Anne ; Aurelle, Marc ; Biascamano, Aldo ; Abe, Koji ; Baxter, Glen ; Rosa, Hervé Di ; Figabella, Dominique ; Deshais, Sabine-Anne ; Baz, Mohamed El ; Cervera, André ; Collin-Thiébaut, Gérard ; Calle, Sophie ; Childress, Nina ; Geoffroy, Christiane ; Vila, Jean-Louis ; Van Doren, Raymond ; Mazuy, Philippe ; Houiller, Sydney ; Gaspari, Rolino ; Helgason, Hallgrimur ; Liagatchey, Violetta ; Mayaux, Philippe ; Lere, Nadine ; Marcel, Didier ; Otero, Agustina ; Vidya & Jean-Michel ; Reip, Hugues ; Trenet, Didier ; Pesce, Anne ; Sigurdsson, Sigurdur Arni ; Hirakawa, Noritoshi ; Monteil, Pascal ; Périmon, Fred ; Napier, Charles ; Hyber, Fabrice ; Lamarche, Bertrand ; Julien, Jacques ; Basserode, Jérôme ; Blocher, Sylvie ; Araki, Nobuyoshi ; Bertrand, Jean-Pierre ; Ducruet, Jérôme ; Fournel, Jacques ; Dezeuze, Vincent ; Feyzdjou, Chohreh ; Chaton, Enna ; Creten, Johan ; Cazal, Philippe ; Closky, Claude ; Giner, Balbino ; Weissman, Benjamin ; Pauvet, Jim ; Brunet, Christel ; Hermann, Matthias ; Friedman, Gabit Eilat & Max ; Hahnenkamp, Maria ; Lhonneur, Jean-Philippe ; Martinez, Patrick ; Bris, Marc Le ; Manche, Matthieu ; Jaffary, M. ; Verna, Jean-Luc ; Zwiller, Franck ; Ramette, Philippe ; Tatu, Pierre ; Perrin, Philippe ; Rullier, Jean-Jacques ; Noël, Cédric ; Mogarra, Joachim ; Parré, Elise ; Muheim, Hélène ; Huyghe, Pierre ; Lachaize, Marion ; Joumard, Veronique ; Barbier, Anne ; etc.
L'Art d'Aimer, curiositas érotica, Nouvelle Vague - Chez le concierge, 11 juillet - 2 septembre 1995
kunstcatalogus